The importance of the taste preferences and sensitivity of mothers and their children in the aspect of excessive body weight of children - Sobek, Grzegorz; Dąbrowski, Mariusz (Frontiers in Endocrinology, 2022)
Food selection among adults and mostly children depends mainly on the taste of a dish. Poor taste sensitivity as well as strong preferences for sweet and fat taste may be of the factors predisposing children to become overweight and/or develop obesity. Family environment, including mothers' eating habits and preferences, may affect children's taste perception and preferences. The aim of the study was to assess taste perception and preferences in children and their mothers in relation to their weight status. Sensory tests were carried out using puddings with different sugar and fat content. The study results did not reveal any differences in the taste sensitivity of overweight/obese and normative body weight children. Similarity was found in the perception of different levels of sweet / fat flavors among children and parents. Overweight / obese children were two times more likely to choose a very fat and very sweet taste compared to normal weight children. The results showed that children prefer a sweet taste more often than their mothers. Mothers' fat taste preferences were important - the fatter the taste they selected, the greater the percentage of children with obesity. Mothers' taste sensitivity may affect children's perception of the quality (intensity) of flavors.